2009
DOI: 10.1080/15287390903248604
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Exposure and Inflammation Markers Among Agricultural Workers in Colorado and Nebraska

Abstract: The adverse respiratory effects of agricultural dust inhalation are mediated in part by endotoxin, a constituent of gram-negative bacterial cell walls. This study quantified personal work-shift exposures to inhalable dust, endotoxin, and its reactive 3-hydroxy fatty acid (3-OHFA) constituents among workers in grain elevators, cattle feedlots, dairies, and on corn farms. Exposures were compared with post-work-shift nasal lavage fluid inflammation markers and respiratory symptoms. Breathing-zone personal air mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 43 publications
1
35
2
Order By: Relevance
“…Our reported geometric mean concentration for personal collected inhalable particulate matter (823 g/m 3 ) and endotoxin (334 EU/m 3 ) was roughly 50% of geometric mean concentrations reported by a study conducted of Wisconsin dairy workers . Higher concentrations were also reported for dairy workers in Colorado and Nebraska, where the inhalable PM fraction was three times higher than what we report for inhalable PM (Burch et al, 2010). In addition the inhalable PM and endotoxin results for personal exposure mean concentrations found here were approximately 60% of those reported from a study conducted in the Netherlands (Spaan et al, 2006).…”
Section: Discussioncontrasting
confidence: 55%
“…Our reported geometric mean concentration for personal collected inhalable particulate matter (823 g/m 3 ) and endotoxin (334 EU/m 3 ) was roughly 50% of geometric mean concentrations reported by a study conducted of Wisconsin dairy workers . Higher concentrations were also reported for dairy workers in Colorado and Nebraska, where the inhalable PM fraction was three times higher than what we report for inhalable PM (Burch et al, 2010). In addition the inhalable PM and endotoxin results for personal exposure mean concentrations found here were approximately 60% of those reported from a study conducted in the Netherlands (Spaan et al, 2006).…”
Section: Discussioncontrasting
confidence: 55%
“…86,89 Previous research has demonstrated the presence of different chain lengths in different agricultural dusts, 86,90,91 and indications exist that different chain lengths are associated with different toxicities. 92,93 To date, application of GC-MS has been limited among others because of a lower sensitivity, when compared with the LAL assay, and an increased cost and labor need for performance. 89,90 Recently, a more sensitive and less laborintensive version of the assay has become available.…”
Section: Methods Of Dust and Endotoxin Determinationmentioning
confidence: 99%
“…Overall, the literature search resulted in 41 publications reporting dust and endotoxin levels from 42 different measurement series among farmers. 12,16,26,90,92, A similar approach was used for literature searches for studies performed in the same period (1980-2012) on determinants of personal exposure to dust and endotoxin using the following terms: personal exposure, exposure determinants, farm characteristics, environmental factors, dust, endotoxin, tasks, pig, poultry, cattle, hog, dust, endotoxin, swine, pig, hog, poultry, broiler, layer, cattle, cow, dairy, farm, farmers, agricultural or agriculture. At least one of the first four of these terms was always included in the searches.…”
Section: Literature Review Methodsmentioning
confidence: 99%
See 2 more Smart Citations